2019
DOI: 10.1136/bmjopen-2019-033393
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index variation over time and associated factors among HIV-positive adults on second-line ART in north-west Ethiopia: a retrospective follow-up study

Abstract: ObjectivesThis study aimed to assess the evolution of body mass index (BMI) of HIV-positive adults on second-line antiretroviral therapy (ART) over time and factors affecting it in north-west Ethiopia.DesignAn institution-based retrospective follow-up study was conducted using data extracted from 1016 patient cards from February 2008 to February 2016.SettingEight referral hospitals from Amhara region, Ethiopia were included.ParticipantsHIV patients who started second-line ART.Outcome measuresChange in BMI sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
4
1
0
Order By: Relevance
“…However, the weight gain rate over time in participants with working functional status was less than participants with ambulatory or bedridden functional status. This finding is consistent with studies conducted elsewhere19 42 and likely reflects HIV disease severity before ART initiation and the return to health in patients with more advanced disease. Finally, there is a higher rate of weight gain among participants who did not take IPT compared with those who took IPT.…”
Section: Discussionsupporting
confidence: 91%
“…However, the weight gain rate over time in participants with working functional status was less than participants with ambulatory or bedridden functional status. This finding is consistent with studies conducted elsewhere19 42 and likely reflects HIV disease severity before ART initiation and the return to health in patients with more advanced disease. Finally, there is a higher rate of weight gain among participants who did not take IPT compared with those who took IPT.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of this study indicated that subjects with ambulatory and bedridden functional status had 2.0 times higher odds to gain ≥10% of their initial weight than those with working functional status. This finding is consistent with other studies conducted elsewhere [ 32–34 ]. In addition, the present study indicated that people with advanced WHO clinical stages (stages III and IV) during ART initiation had 1.78 times higher odds to gain ≥10% of their initial weight than those with mild clinical stages (stages I and II).…”
Section: Discussionsupporting
confidence: 94%
“…The average BMI level is increased by 0.2 kg/m 2 for a one-unit increase in the ART follow -up number of HIV-positive adults. This finding is consistent with prior related studies conducted in Ethiopia 32 35 , Tanzania 36 , South Africa 37 , 38 , and United States America 39 . The increase in BMI level over time in patients who are on ART could be due to the reduction in the metabolic demand of body cells 40 , the reversal of HIV-associated catabolism 41 , the return of gastrointestinal function, the decreased incidence of opportunistic infections 20 , 21 and the redistribution of fat as a component of Lipodystrophy 42 , 43 .…”
Section: Discussionsupporting
confidence: 93%
“…The BMI increment status of HIV-positive adults with advanced HIV stages is low compared to patients with WHO stages I or II clinical illnesses. The finding is supported by prior studies conducted in Ethiopia 25 , 32 , 34 , 54 , Zimbabwe 55 , Nepal 56 and USA 40 . The decline in BMI status might be due to the presence of high nutritional requirements or calorie expenditures and the poor appetite and absorption of nutrients in individuals with advanced-stage clinical disease 4 .…”
Section: Discussionsupporting
confidence: 82%